2023
DOI: 10.1039/d2bm01357f
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast-targeting polymeric nanovehicles to enhance topical wound healing through promotion of PAR-2 receptor-mediated endocytosis

Abstract: The level of collagen production critically determines skin wound contraction. If an intelligent skin drug delivery technology that enables the collagen production in a specific wound skin area is developed,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Unlike the consistent temporal expression of PAR-2 in skin cells [ 20 , 22 , 23 ], an important finding in the current work is that MMP-2 and -9 expression during wound healing was not only divergent among cell types but, importantly, altered over time. Consistently with the literature [ 45 ], our IHC showed that MMP-9 was primarily produced by the leading edge of the epithelial tongue and peaked at days 1 and 3.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Unlike the consistent temporal expression of PAR-2 in skin cells [ 20 , 22 , 23 ], an important finding in the current work is that MMP-2 and -9 expression during wound healing was not only divergent among cell types but, importantly, altered over time. Consistently with the literature [ 45 ], our IHC showed that MMP-9 was primarily produced by the leading edge of the epithelial tongue and peaked at days 1 and 3.…”
Section: Discussionmentioning
confidence: 67%
“…Once activated, PAR-2 initiates a cascade of intracellular events leading to diverse cellular responses [ 10 , 36 , 38 ]. One prominent downstream effect of PAR-2 activation is the modulation of MMP expression, particularly MMP-2 and MMP-9 [ 23 , 24 ]. The relationship between PAR-2 and MMP-2 and -9 production has been established in various physiological and pathological contexts [ 10 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lee and his co-workers developed a smart fibroblast targeting PMs via binding overexpressed PARs-2 for better wound healing performance. 144 Targeted PMs comprised amphiphilic PEO- b -PCL followed by functionalization with KTTKS; a collagen-derived peptide via thiol–maleimide conjugation technique 22 to form KTTKS/PEO- b -PCL nanomicelles. The inner core of the targeted micelles was loaded with CUR through hydrophobic interaction to give KTTKS/PEO- b -PCL-CUR nanomicelles.…”
Section: Polymeric Micelles For Targeting Different Receptorsmentioning
confidence: 99%